Data visualization on focus: exploring communicability of dashboards generated from BI tools - Nunes, Felipe; Correa, Claiton; Jandrey, Alessandra; Barcelos, Allan; Reyes, Daniel; Bernardes, Matheus; Sales, Afonso; Silveira, Milene Selbach (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2020: Anais do XIX Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2020)
Technological evolution has led to the development of an increasingly connected society, in which the volume and variety of data generated grow constantly. In this context, data visualization becomes a challenge, since it has the potential to facilitate users’ understanding of the analyzed data. Nowadays, there are several tools to support the construction of visualizations, each one offering resources for the construction of dashboards from a set of data. Considering this scenario and based on the application of semiotic inspection and communicability assessment methods, this study presents an analysis of three visualization tools available on the market (Tableau, Power BI and Zoho Analytics), in order to understand the interaction of users with the developed visualizations and to identify possible existing communicability problems. We used the 2010 Brazilian Census data to build dashboards in these three tools as a method of validating our study. The results show a greater number of communication disruptions in the interaction with Tableau and Power BI in relation to Zoho Analytics, indicating that Zoho Analytics allows the user a greater understanding of the result of the actions taken.